2008
DOI: 10.1002/psc.992
|View full text |Cite
|
Sign up to set email alerts
|

Kissper, a kiwi fruit peptide with channel‐like activity: Structural and functional features

Abstract: Kissper is a 39-residue peptide isolated from kiwi fruit (Actinidia deliciosa). Its primary structure, elucidated by direct protein sequencing, is identical to the N-terminal region of kiwellin, a recently reported kiwi fruit allergenic protein, suggesting that kissper derives from the in vivo processing of kiwellin. The peptide does not show high sequence identity with any other polypeptide of known function. However, it displays a pattern of cysteines similar, but not identical, to those observed in some pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…The channel activity of Kissper might depend on hydrophobic and hydrophilic interactions of the Kissper molecules with membrane lipids, as suggested for some bioactive peptides. This result is confirmed by our previous study in which we showed that kissper interacts with lipid bilayers forming channel-like pores with anion selectivity in KCl [18].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The channel activity of Kissper might depend on hydrophobic and hydrophilic interactions of the Kissper molecules with membrane lipids, as suggested for some bioactive peptides. This result is confirmed by our previous study in which we showed that kissper interacts with lipid bilayers forming channel-like pores with anion selectivity in KCl [18].…”
Section: Discussionsupporting
confidence: 90%
“…PLMs made up of DOPS:DOPE:POPC (27:27:18, w:w:w) in 1% n-decane (Fluka) were formed as previously described [18,22]. The channel current was monitored in different salt solutions, i.e.…”
Section: Single Channel Measurementmentioning
confidence: 99%
See 3 more Smart Citations